Development of an International Qualification Framework for the Strength and Conditioning Profession: International Universities Strength and Conditioning Association Position Statement - International Journal of Strength and Conditioning; Andrew Langford; Aden Flannagan; Paulo H. Marchetti; Stephen P. Bird (International Universities Strength and Conditioning Association, 2024)
In the profession of strength and conditioning (S&C), there is a need for a standardised, comprehensive framework that can allow for the alignment of international certifications, qualifications, and standards. This need stems from the lack of clarity surrounding the awarding levels of different governing bodies and organisations worldwide, as well as the increased connectedness of international sport and physical activity. Central to such a framework is understanding the current issues affecting S&C coaches,1 current professional standards and guidelines,2 and remuneration structures.3,4 As the sole dedicated international accreditation body, the International Universities Strength and Conditioning Association (IUSCA)5 carried out market research analysis and stakeholder engagement with regional and international educational authorities (Ofqual, European Commission, UNESCO, USDE, CHEA, TEQSA, ASQA) to develop a global framework for the rating and awarding of S&C courses, certifications, and qualifications.